2010
DOI: 10.1086/652778
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Molecular Fingerprinting of Methicillin-ResistantStaphylococcus aureusNasal Colonization in Different Patient Populations: A Prospective, Multicenter Study

Abstract: Nasal swab specimens positive for MRSA had a geometric mean quantity of 794 CFU per swab, with great diversity in the quantity of MRSA at this anatomic site. Outpatient populations at high risk for MRSA carriage were elderly residents of long-term care facilities, HIV-infected outpatients, and outpatients receiving hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
2
24
2
Order By: Relevance
“…At 11.5% prevalence, the USA500/Iberian type was the most frequently isolated strain in our population, representing 48.0% of the MRSA isolates recovered from the groin and 57.4% from the nares. This is higher than the reported prevalence of USA500 among HIV-infected patients in Dallas, TX, and New York City (range, 4.8 to 5.6%) (8,49) but lower than the reported prevalence (19%) among general patients screened at admission to another Atlanta-area hospital (21), and both USA300 and USA500 colonization has been associated with HIV infection (36).…”
Section: Discussioncontrasting
confidence: 61%
“…At 11.5% prevalence, the USA500/Iberian type was the most frequently isolated strain in our population, representing 48.0% of the MRSA isolates recovered from the groin and 57.4% from the nares. This is higher than the reported prevalence of USA500 among HIV-infected patients in Dallas, TX, and New York City (range, 4.8 to 5.6%) (8,49) but lower than the reported prevalence (19%) among general patients screened at admission to another Atlanta-area hospital (21), and both USA300 and USA500 colonization has been associated with HIV infection (36).…”
Section: Discussioncontrasting
confidence: 61%
“…Persistent S. aureus carriers have been found to carry a greater quantity of S. aureus in their noses (measured in log 10 CFU per nares culture) than intermittent carriers (46). Average S. aureus bacterial loads among nasal carriers tend to range between 1.8 and 2.9 log 10 CFU per nares culture (47,48). One study found that this load increased among MRSA carriers when patients received antibiotics that did not have activity against MRSA (e.g., beta-lactams or fluoroquinolones) (48).…”
mentioning
confidence: 99%
“…The prevalence of USA300 in varied patient populations in the USA has been reported to range from 10 to almost 70 % among S. aureus isolates (Mermel et al, 2010). Using the sensitivity and specificity as determined above for the USA300 family isolates, this resulted in post-test probabilities of 47 % (positive test) and 2 % (negative test) for 10 % prevalence, and 95 % (positive test) and 26 % (negative test) for 70 % prevalence.…”
Section: Resultsmentioning
confidence: 99%